Boquila trifoliolata mimics leaves of an artificial plastic host plant. (31st December 2022) - White, Jacob; Yamashita, Felipe
ABSTRACT: Upon discovery that the Boquila trifoliolata is capable of flexible leaf mimicry, the question of the mechanism behind this ability has been unanswered. Here, we demonstrate that plant vision possibly via plant-specific ocelli is a plausible hypothesis. A simple experiment by placing an artificial vine model above the living plants has shown that these will attempt to mimic the artificial leaves. The experiment has been carried out with multiple plants, and each plant has shown attempts at mimicry. It was observed that mimic leaves showed altered leaf areas, perimeters, lengths, and widths compared to non-mimic leaves. We have calculated four morphometrical features and observed that mimic leaves showed higher aspect ratio and lower rectangularity and form factor compared to non-mimic leaves. In addition, we have observed differences in the leaf venation patterns, with the mimic leaves having less dense vascular networks, thinner vascular strands, and lower numbers of free-ending veinlets.